Comparison of One vs. Two BACTEC Myco/F Lytic Bottles for Recovery of Fungi and Mycobacteria - Ramanan, Poornima (Open Forum Infect Dis, 2017)
BACKGROUND: The BACTEC Myco/F Lytic bottle (Becton Dickinson), along with the Wampole Isolator lysis centrifugation tube (Alere) are used to enhance recovery of fungal and mycobacterial organisms from blood. At our institution, one Isolator tube and two Myco/F Lytic bottles are inoculated for each suspected case of fungemia or mycobacteremia. A retrospective analysis of 7518 cultures over 6 years was performed to determine whether one or twoMyco/F Lytic bottles were required for optimal recovery of these organisms. METHODS: Blood was collected by a phlebotomy team and distributed into three blood culture receptacles: 2 Myco/F Lytic bottles each with 4 mL of blood and one Isolator tube with 8 mL of blood. The sediment from the processed Isolator tube was inoculated onto Inhibitory Mold Agar, Emmons Sabouraud Dextrose Agar, and Middlebrook 7H11/7H11 Selective Agar. The Myco/F Lytic bottles were incubated for 42 days on the BACTEC FX instrument and the plated media was incubated for 30 days. We compared the recovery of fungal and mycobacterial organisms from one vs. two Myco/F Lytic bottles at our institution from April, 2004 through October, 2010. Myco/F Lytic bottles were randomly assigned as the first or second bottles and additional culture positivity results for the second bottle was compared with that of the first bottle and the Isolator tube together. RESULTS: 171 (2.3%) cultures were positive with fungal or mycobacterial isolates from a total of 7518 cultures. Among 171 positive cultures, 28 (16.4%) grew only in the second Myco/F Lytic bottle. Among these, 20 were fungi (Histoplasma capsulatum, n = 7, Candida sp., n = 7, filamentous fungi, n = 4, Cryptococcus neoformans, n = 1, other yeast, n = 1), 7 were mycobacterial species (Mycobacterium avium complex, n = 7) and 1 was an aerobic actinomycete (Streptomyces sp). 7/45 (15.6%) of H. capsulatum isolates, 7/18 (38.9%) of M.avium complex isolates and 1/17 (5.9%) of C.neoformans isolates grew in the second Myco/F Lytic bottle only. CONCLUSION: The use of two Myco/F Lytic bottles increases the recovery of certain fungal and mycobacterial organisms from blood as compared with one Myco/F Lytic bottle. DISCLOSURES: All authors: No reported disclosures.